Quality Management Strategy of Talent Training in Universities under Liaoning Provenience - huili, tan; Howattanakul, Sutida; Pruettikul , Sataporn (Nimitmai Review Journal, 2024)
The objectives of this research were 1)Investigate the constituent factors of talent training quality management in universities under Liaoning Province. 2) Propose on quality management strategy of talent training in universities in liaoning province. This research was a mixed method study. Population were the Population is the Managements、Administrators and Instructors of 20 universities under Liaoning Province who have many years of experience in talent training and quality management. Use Krejcie and Morgan (1970) sampling a total of 270. There are five key informants, namely experts and scholars in talent training and quality management. Obtained by purposeful sampling. The instrument used a semi-structured interview form, questionnaire and focus group discussion form. The research is divided into three processes: research scheme preparation, research procedure and research report. The statistical data used for data analysis are: data analysis includes frequency, percentage, average value, standard deviation and the combination of exploratory factor analysis and content analysis. The results show that: 1) The research object has six components: including the process management of talent training quality, improving teachers’ teaching quality and students’ learning ability, the evaluation system and achievement management of talent training, perfecting the management system of teachers and students, improving the participation of teachers and students and innovating the quality management system of talent training; And 2) 15 strategies for talent training quality management in Universities under Liaoning Province: there are two strategies for talent training quality process management, three strategies for improving teachers’ teaching quality and students’ learning ability, three strategies for talent training evaluation system and achievement management, three strategies for improving teachers’ and students’ management system, two strategies for improving teachers’ and students’ participation, and two strategies for innovating talent training quality management system.